Millipede gut-derived microbes as a potential source of cellulolytic enzymes - Koubová, Anna; Lorenc, František; Horváthová, Terézia; Chroňáková, Alica; Šustr, Vladimír (World journal of microbiology & biotechnology, 2023)
Lignocellulose biomass has recently been considered a cost-effective and renewable energy source within circular economy management. Cellulases are important key enzymes for simple, fast, and clean biomass decomposition. The intestinal tract of millipedes is the environment which can provide promising microbial strains with cellulolytic potential. In the present study, we used the tropical millipede Telodeinopus aoutii as an experimental organism. Within a feeding test in which millipedes were fed with oak and maple leaf litter, we focused on isolating culturable cellulolytic microbiota from the millipede gut. Several growth media selecting for actinobacteria, bacteria, and fungi have been used to cultivate microbial strains with cellulolytic activities. Our results showed that oak-fed millipedes provided a higher number of culturable bacteria and a more diversified microbial community than maple-fed ones. The screening for cellulolytic activity using Congo red revealed that about 30% of bacterial and fungal phylotypes isolated from the gut content of T. aoutii, produced active cellulases in vitro. Actinobacteria Streptomyces and Kitasatospora were the most active cellulolytic genera on Congo red test. In contrast, fungi Aspergillus, Penicillium, Cheatomium, Clonostachys, and Trichoderma showed the highest protein-specific cellulase activity quantified by 4-Methylumbelliferyl β-D-cellobioside (4-MUC). Our findings provide a basis for future research on the enzyme activities of microbes isolated from the digestive tracts of invertebrates and their biocatalytic role in biomass degradation.
Keywords: celulasy; Congo Red; Diplopoda; Cellulase; Invertebrates; Fungi; Cellulases; Intestine; Bacteria; celulasa; Actinobacteria; Kongo červeň